A palladium and gold catalytic system enables direct access to O- and S-linked non-natural glyco-conjugates. Issue 48 (25th November 2016) - Jeon, Min Ho; Mathew, Bijoy P.; Kuram, Malleswara Rao; Myung, Kyungjae; Hong, Sung You
Abstract : A Pd/Au-catalyzed Sonogashira reaction allows the direct synthesis of O - and S -linked non-natural glyco-conjugates. Abstract : Here we report a straightforward cross-coupling method for the synthesis of non-natural glycoamino acids from alkyne-bearing monosaccharides and p -iodophenylalanine. Pd/Au-catalyzed Sonogashira coupling is tolerant to both O - and S -glycosides without any epimerization. In addition, no racemization of the amino acid was observed allowing direct access to the homogeneous glyco-conjugate in a single step. Notably, this Pd/Au catalytic system presents enhanced catalytic activity than conventional Pd/Cu and Pd-only platforms, and it further enables the convergent synthesis of glycodipeptides.